Lei de responsabilidade fiscal: seu impacto no controle da despesa com pessoal no município de Aracaju (período 2000-2017) - Emmerick, Alexandre Conti (2019)
Historically, the fiscal imbalance was the rule in the Brazilian Public Administration. As a result of this situation, the Fiscal Responsibility Law (LRF) was published with the purpose of assisting managers of public resources through a clear and precise rules framework, applicable to all administrators, in all spheres of government, regarding the management of public revenue and expenditure, indebtedness and the management of public assets. In this context, the present work constitutes a descriptive and quantitative research that aimed to analyze the influence of the Law of Fiscal Responsibility in the total expenditure with personnel of the city of Aracaju. To do so, it is part of a comparative study of data from the 75 municipalities of the State of Sergipe, in a selected time series, from 1999 to 2017, using as a parameter information from Finance of Brazil -FINBRA, a database prepared by the National Treasury Secretariat on expenditures with personnel and current net revenue, as well as the databases of the Audit Court of Sergipe, namely the Public Audit System - SISAP and the Company Resources Management Monitoring System - SAGRES. In order to delimit the time frame, two scenarios are drawn, the financial year prior to the law and financial years after the law, on the basis of which the behavior of personnel expenses in relation to net of time. In the end, it was concluded that, despite the fact that for a large part of the period under review, personnel expenses remained within the established legal percentage, the LRF proved incapable of containing the real increase in personnel expenses.